Measurement of the tt̄ production cross section in pp̄ collisions at √s=1.96TeV using soft electron b-tagging - Aaltonen, T; Adelman, J; Akimoto, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2010)
We present a measurement of the top-quark pair-production cross section in pp̄ collisions at √s=1.96TeV using a data sample corresponding to 1.7fb-1 of integrated luminosity collected with the Collider Detector at Fermilab. We reconstruct tt̄ events in the lepton+jets channel, consisting of eν+jets and μν+jets final states. The dominant background is the production of W bosons in association with multiple jets. To suppress this background, we identify electrons from the semileptonic decay of heavy-flavor jets ("soft electron tags"). From a sample of 2196 candidate events, we obtain 120 tagged events with a background expectation of 51±3 events, corresponding to a cross section of σtt̄=7. 8±2.4(stat)±1.6(syst)±0.5(lumi)pb. We assume a top-quark mass of 175GeV/c2. This is the first measurement of the tt̄ cross section with soft electron tags in run II of the Tevatron. © 2010 The American Physical Society.